EXPLORING KEY BARRIERS TO PLANT-BASED MEAT ACCEPTANCE IN MALAYSIA: SENSORY, PRICE, NUTRITION, AND AVAILABILITY DIMENSIONS - Mohd Zahari, Mohd Salehuddin; Piah, Zul Hazam Mohd; Fuza, Zatul Iffah Mohd; Abdullah, Nor Hidayah; Abidin, Izhar Hafifi Zainal (JOURNAL OF TOURISM, HOSPITALITY AND ENVIRONMENT MANAGEMENT (JTHEM), 2025)
The global movement toward a plant-based diet and lifestyle, known as the Plant-Based Revolution, has gained substantial traction in recent years due to its potential benefits for personal health, environmental sustainability, and animal welfare. However, the growing awareness and availability of plant-based options, the widespread adoption of this revolution faces various barriers that hinder its acceptance across diverse populations. This conceptual paper delves into an extensive review of existing literature on the plant-based movement, including its documented health benefits, ecological advantages, evolving consumer attitudes, and the multifaceted barriers impeding its broader societal integration. Drawing upon these interdisciplinary insights, a conceptual framework is proposed. This framework integrates key constructs such as sensory perception, price sensitivity, nutritional skepticism, and product availability each representing salient inhibitors frequently cited in extant literature. Furthermore, the framework is proposed to conceptualize within Malaysia’s diverse demographic landscape. The model aims to elucidate the interplay between these variables and their influence on consumer resistance or acceptance, thereby offering a comprehensive lens through which behavioral patterns can be better understood. Ultimately, this proposed framework not only guide for empirical investigations but contributes both theoretical and practical implications.